On the development of flight-test equipment in relation to the aircraft spin - Bennett, Christopher J.; Lawson, Nicholas J. (Elsevier, 2018)
A review of the development of flight test equipment throughout aviation history is presented, focusing specifically on the stall spin. The primitive, yet, ingenious solutions devised in the early twentieth century by the pioneers of this field, paved the way for the advancement in knowledge of the complex aerodynamic properties inherent during a spin. Both in Britain and the US, the dangers associated with stalling and spinning were acknowledged shortly after the birth of aviation, with pilots and academics alike seeking to investigate the causes. Initially, the goal was to design safer aircraft, with more predictable handling, dynamic manoeuvrability, and precise controllability. Both nations were able to independently develop equipment packs which were to become standard for airborne investigations of the spin and other manoeuvres in the following years. These early studies laid the foundations on which we're still building today, now using state-of-the-art technology to enhance our knowledge of spin dynamics ever further.